Components of the language-ready brain - Antonio Benitez-Burraco (Frontiers Research Topics, 2016)
This volume highlights new avenues of research in the language sciences, and particularly, in the neurobiology of language. The term "language-ready brain" stresses, on the one hand, the importance of a brain-based description of our species' linguistic capacity, and, on the other, the need to appreciate the crucial role culture plays in shaping the linguistic systems children acquire and adults use. For this reason, the focus is not put on language per se, but on our learning biases and cognitive pre-dispositions toward language. Both brain and culture are considered at two crucial levels of inquiry: phylogeny and ontogeny. In a fast-growing field like the language sciences and specifically, language evolution studies, this book has tried to capture several of the most exciting topics explored currently, sowing seeds for future investigations.